Block-diagonal algebras of analytic functions on Banach spaces - Taras, O.G. (Carpathian Mathematical Publications, 2012)
In this work we consider about algebras block diagonal of analytic functions on the space $\ell_1$ and $\ell_2$ and investigate spectra of these algebras.